A Lady with Generalized Nodular Lesions - Ho Tung Wong; Tin Wai Chay; Chi Kit Au; Tin Lok Lai (Journal of Clinical Rheumatology and Immunology)
This clinical quiz discusses a condition that can cause generalized nodular lesions, its underlying immunological reactions, and its management.